Odontogenic Diseases And Disorders Of Infectious Nature In Relation To Paediatric Population–A systematic review - Shunmugavelu, Karthik; Saravanan, Jayakanthan; Jyoti, Sapna (Journal of Neonatal Surgery, 2025)
Background: Most Odontogenic tumors that affect children and adolescents are benign and constitute about 1% to as high as 28% of all oral lesions in children. It is important to know that the reported frequency of odontogenic tumors in the pediatric age group may likely be related to ethnic or geographic consideration of the population studied. This systematic review presents the detailed data about the occurrence of pediatric odontogenic tumors, the predominant type of tumor, most common sites, gender predominance and so on. Materials and Methods: A systematic literature review and retrospective studies of Pediatric odontogenic tumors published in two electronic databases was conducted based on the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) Statement. Results:The predominant odontogenic tumor that was reported is Odontoma which accounted to 641 cases which was 52% of the total cases reported under the age of 20. Following Odontoma, it was Ameloblastoma which was 36% with 448 cases reported. Next in line were Keratocystic odontogenic tumors (147) and Adenomatoid Odontogenic tumor (116). The other odontogenic tumors that were encountered in the studies are Cementoblastoma(15), Ameloblaic fibroodontoma(48),Ameloblasticfibroma(56),Odontogenicmyxoma(96), Odontogenicfibroma (75) and Calcifying epithelial odontogenictumor(19). Conclusion:The result of the study was in line with the previous literature reviews suggesting that even though Pediatric odontogenictumorsareuncommonandusuallypresentsasbenigntumors,themalignantvariants dooccur and the detailed information regarding it is necessary for the better understanding of the tumor in regard to treatment.